2017
DOI: 10.1080/1068316x.2017.1296149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating interviews which search for the truth with suspects: but are investigators’ self-assessments of their own skills truthful ones?

Abstract: Self-evaluation of one's own performance has been found in prior research to be an enabler of professional development. The task of evaluation is also a core component of a model of the investigative interviewing of victims, witnesses and suspects, being increasingly used throughout the world. However, it remains the case that there has been little research as to how practitioners approach the task itself. The present study examined the topic through the lens of observing how effectively 30 real-life investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 83 publications
1
28
0
Order By: Relevance
“…Self-efficacy has also been found to be associated with employee motivation and effort when learning difficult tasks (Lunenberg 2011). Walsh et al (2017) found, in their study of investigators, a self-confidence about own interviewing ability, which, in turn, was found consistently inferior to that objectively assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-efficacy has also been found to be associated with employee motivation and effort when learning difficult tasks (Lunenberg 2011). Walsh et al (2017) found, in their study of investigators, a self-confidence about own interviewing ability, which, in turn, was found consistently inferior to that objectively assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Griffiths (2008) found that planning is a complex task. However, investigators have been found to possess little self-awareness of how poor were their own planning skills (Walsh et al 2017). Griffiths and Walsh (submitted) found that more accurate self-awareness was only apparent when investigators exercised skilled reflection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a dearth of literature concerning how (and how effectively) law enforcement officers reflect and evaluate their own performance. A recent study, undertaken by Walsh, King, and Griffiths (2017), found that investigators regularly over-rated their own interview performance when compared to that of an independent expert. In that study, the participants assessed their own interview performance across 30 behavioural dimensions, using a five-point Likert scale.…”
Section: Qualitative Analysis Of Qualitative Evaluation: An Exploratomentioning
confidence: 99%
“…In practice, police detectives are the ones to create a first impression of the suspect's alibi's believability. The initial suspect interviews are a key investigative act in the criminal investigation (Baldwin, 1993;Norfolk & Stark, 2011;Walsh, King, & Griffiths, 2017). The gathered information in those interviews is crucial for the further development of the investigation in the light of the evidence being gathered; for example: when CCTV footage is available, those tapes should be collected as soon as possible to reduce the risk that the tapes will no longer be available.…”
Section: The Evaluation Of Alibis By Students and Police Detectivesmentioning
confidence: 99%